2009
DOI: 10.1164/rccm.200905-0740oc
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Drives Autocrine Epithelial Cell Proliferation and Survival in Chronic Rhinosinusitis with Nasal Polyposis

Abstract: These data demonstrate that VEGF is a novel biomarker for chronic rhinosinusitis with hyperplastic sinonasal polyposis that functions in an autocrine feed-forward manner to promote nasal epithelial cell growth and to inhibit apoptosis. These findings implicate a previously unrecognized and novel role of VEGF functioning through neuropilin-1 on nonneoplastic primary human airway epithelial cells, to amplify cell growth, contributing to exuberant hyperplastic polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 72 publications
6
54
1
Order By: Relevance
“…The present study provides evidence supporting an important role for VEGF in the pathogenesis of nasal polyposis, as we measured significantly high levels of mRNA expression both for VEGF and its receptor FLT-1 in nasal polyps compared to control turbinate mucosa. These findings are in accordance with recent literature (20)(21)(22)(23)(24), although, to the best of our know ledge, this is the first study to report mRNA expression levels of both VEGF and its receptor FLT-1 in human nasal polyp tissue. Mounting evidence suggests that, besides its influence on blood vessel formation, VEGF may even be directly involved in the pathogenesis of bronchial asthma (30,31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study provides evidence supporting an important role for VEGF in the pathogenesis of nasal polyposis, as we measured significantly high levels of mRNA expression both for VEGF and its receptor FLT-1 in nasal polyps compared to control turbinate mucosa. These findings are in accordance with recent literature (20)(21)(22)(23)(24), although, to the best of our know ledge, this is the first study to report mRNA expression levels of both VEGF and its receptor FLT-1 in human nasal polyp tissue. Mounting evidence suggests that, besides its influence on blood vessel formation, VEGF may even be directly involved in the pathogenesis of bronchial asthma (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…Our main finding was the increased expression of mRNA levels of VEGF, FLT-1, Ang-1, Ang-2, Tie-2A, Tie-2B, SDF-1α and SDF-1β in NP tissue samples compared to normal turbinate tissue samples. There is conflicting evidence regarding the exact role of angiogenic growth factors in the pathophysio logy of nasal polyposis (20)(21)(22)(23)(24). It has been suggested that proangiogenic factors are involved in the disease process through the formation of edema, the activation of inflammatory cell migration and activation of the nitric oxide synthase pathway (13,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor is up-regulated in CRSwNP and drives epithelial cell proliferation. 22 In particular, VEGF-A has neurotrophic effects and has been proposed as a potential therapy for neurodegenerative disorders.23 It is possible that the positive correlation we found is due to increased vascularization and improved olfactory neuron function, but this is purely speculative.…”
Section: Discussionmentioning
confidence: 88%
“…Alternatively, epithelial VEGF-A may not be associated with peribronchial angiogenesis in CF subjects and may play different roles (e.g. epithelial proliferation [33]). CF subjects at transplantation were younger than control subjects.…”
Section: Discussionmentioning
confidence: 99%